Biological activities of medicinal plants used in Veterinary Medicine in Brazil between 2000 and 2020: A literature review (Research, Society and Development, 2021)
The treatment of diseases based on medicinal plants is an old practice that has gaining special attention in the area of medical science, especially in veterinary medicine, where several scientific studies have already proven the effectiveness of countless plants as a possible alternative to the use of conventional drugs. In this perspective, the objective of this literature review was to gather scientific studies carried out in Brazil on the therapeutic efficacy of medicinal plants with possible application in veterinary medicine. To this end, 114 articles (searched in Google Academic, SciELO, PubMed, Science Direct and MEDLINE databases) were selected to compose this review. The biological activity of more than 70 plants has been proven, concluding that plants are efficient and safe alternatives for the treatment of diseases in veterinary medicine.